Strain glass in Ti50-x-yNi50+yNby alloys exhibiting a boson peak glassy anomaly. (February 2023) - Lin, Hongji; Ren, Shuai; Dang, Pengfei; Hao, Chunxi; Tao, Xuefei; Xue, Dezhen; Wang, Yu; Zong, Hongxiang; Zhang, Zhenxuan; Ruan, Wenqing; Liang, Xiong; Ma, Jiang; et al.
Abstract: Strain glass, which is a type of ferroic glass with lattice strain short-range ordering, has been found in many shape memory alloy systems, while its unique properties still await to be investigated. Here we report a strain glass found in Ti50- x - y Ni50+ y Nb x due to the synergistic effect of Ni and Nb atoms and its boson peak glassy anomaly. It is found that Nb atoms can only slightly suppress the martensitic transformation, but with the help of 1 at% excess Ni atoms ( y =1), 2% Nb atoms ( x =2) are enough to lead the system to the strain glass state. A three-dimensional phase diagram is established accordingly. Moreover, a boson-peak-like glassy feature is also found in the strain glass state, which resembles the boson peak in metallic glass. This work provides more clues to understand the glass nature of strain glass. Graphical abstract: Image, graphical abstract